Factors associated with oral health service utilization among young people in southern China - Yunquan Cai; Shaobo Zeng; Yimei Hu; Lingfeng Xiao; Yanqing Liao; Zihui Yan; Wenxiang Zha; Junwang Gu; Qi Wang; Ming Hao; Chunmei Wu (BMC, 2024)
Abstract Objectives To identify the patterns and influencing factors of oral health service utilization among college students, and further to provide scientific evidence for policy making on oral health education and behavioral interventions for the college population. Methods The study population was college students in Southern China. Totally 678 students participated in the survey. A self-designed questionnaire based on Anderson's model (predisposing factors, enabling factors, need factors) was used to survey college students. Descriptive statistics, χ2 test, and logistic regression were used to analyze influence factors of oral health service utilization among college students. Results The utilization rate of oral health service in the past 12 months was 30.2%. The primary type of oral health service was treatment (59.6%), and only 12.8% were for prevention. There were 39% of the participants having oral health diseases, of which dental caries (25.7%) and oral bleeding (22.2%) were the main problems. The results from logistic regression analysis revealed that students with better beliefs (OR = 1.84, 95% CI:=1.02-3.43), frequent consumption of sugary drinks (OR = 2.90, 95% CI:=1.90-4.47), teeth brushing frequency > = 2 times per day (OR = 2.09, 95% CI = 1.24-3.61), frequent floss utilization (OR = 2.63, 95% CI = 1.21-5.76), dental caries (OR = 2.07, 95% CI = 1.35-3.17) used oral health services higher, while those lived in rural areas (OR:0.52, 95% CI = 0.34-0.80), and had only a fair concern (OR = 0.48, 95% CI = 0.31-0.74) or no concern (OR = 0.26, 95% CI = 0.08-0.67) on oral health utilized oral health services lower. Conclusions Chinese college students demonstrate some knowledge and attitudes towards oral health. However, they tend to neglect oral hygiene and have limited understanding of their own oral issues. Furthermore, the utilization of oral services, such as treatment, remains remarkably low, despite the availability of long-term and favorable health insurance policies. The utilization of oral health services among college students is influenced by various factors, including residing in rural areas, consuming sugary beverages on a daily basis, brushing teeth at least twice a day, and practicing flossing.